Carbapenemase genes distribution in clonal lineages of Acinetobacter baumannii: a comprehensive study on plasmids and chromosomes - Beig, Masoumeh; Badmasti, Farzad; Solgi, Hamid; Nikbin, Vajihe Sadat; Sholeh, Mohammad (Frontiers in Cellular and Infection Microbiology, 2023)
The global spread of plasmids carrying carbapenemase genes within carbapenem resistant Acinetobacter baumannii (CRAB) strains poses a worldwide public health issue. In this study, we conducted a comprehensive genetic analysis of plasmids and chromosomes harboring the major carbapenemase genes (blaNDM, blaKPC, blaVIM, blaIMP, blaGES, in CRAB strains using bioinformatic tools.We retrieved plasmids and chromosomes carrying the major carbapenemase genes from GenBank. The size, replicon type, and conjugal apparatus of the plasmids were also determined. Furthermore, allele types, co-existence of other antimicrobial resistance genes alongside carbapenemases in plasmids or chromosomes, co-occurrence of carbapenemase genes, gene repetition, and sequence types (ST) of whole genomes were characterized.The database contained 113 plasmids and 38 chromosomes harboring carbapenemase genes. This investigation revealed that blaNDM and blaOXA-58-like were the predominant allele types in both the plasmids and chromosomes. Nine (7.96%) plasmids with blaNDM-1 were potentially conjugative. The most common replicon types of the plasmids were R3-T1, R3-T8, R3-T2, R3-T23, and RP-T1. The analysis revealed that blaNDM-1 and blaOXA-58-like genes possessed the highest variety of co-existence with other antibiotic resistance genes. The co-occurrence of dual carbapenemases was identified in 12 plasmids and 19 chromosomes. Carbapenemase gene repetitions were identified in 10 plasmids and one chromosome. Circular alignment revealed that the plasmids carrying the co-occurrence of blaNDM-1 and blaOXA-58 were more homogeneous.However, there was heterogeneity in certain regions of these plasmids. According to the minimum spanning tree (MST) results, the majority of the plasmids belonged to the genomes of ST2 Pas , ST1 Pas , ST422 Pas , ST622 Pas , and ST85 Pas .3 Conclusion: A. baumannii appears to have a strong ability for genome plasticity to incorporate carbapenemase genes on its plasmids and chromosomes to develop resistance against carbapenems. Mobilizable plasmids harboring carbapenemases significantly contribute to the dissemination of these genes. The genetic structure of the plasmids revealed a strong associations of class I integrons, ISAba-like structures, Tn4401 elements, and aac (6′)-Ib with carbapenemases.Furthermore, gene repetition may also be associated with carbapenem heteroresistance.